2011
DOI: 10.4142/jvs.2011.12.4.393
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of glomerular filtration rate with dynamic computed tomography in normal Beagle dogs

Abstract: The objective of our study was to determine individual and global glomerular filtration rates (GFRs) using dynamic renal computed tomography (CT) in Beagle dogs. Twenty-four healthy Beagle dogs were included in the experiment. Anesthesia was induced in all dogs by using propofol and isoflurane prior to CT examination. A single slice of the kidney was sequentially scanned after a bolus intravenous injection of contrast material (iohexol, 1 mL/kg, 300 mgI/mL). Time attenuation curves were created and contrast cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
0
17
2
Order By: Relevance
“…Contrast studies, such as the excretory urogram, or more advanced techniques, such as computerised tomography or magnetic resonance imaging with contrast, may provide additional information regarding the patency of the urinary system and the presence of abnormalities (Ohlerth & O'Brien 2007 , Chang et al . 2011 , Fonseca-Matheus et al . 2011 , Schmidt et al .…”
Section: Resultsmentioning
confidence: 99%
“…Contrast studies, such as the excretory urogram, or more advanced techniques, such as computerised tomography or magnetic resonance imaging with contrast, may provide additional information regarding the patency of the urinary system and the presence of abnormalities (Ohlerth & O'Brien 2007 , Chang et al . 2011 , Fonseca-Matheus et al . 2011 , Schmidt et al .…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, we examined only the left kidney (left kidney), because it is impossible to perform CEUS on both kidneys simultaneously. A study that evaluated glomerular filtration rate with dynamic computed tomography in normal dogs reported that contrast agent concentrations and glomerular filtration rate were not significantly different between the left and right kidneys [ 2 ]. Therefore, it is thought that the perfusion of one kidney is similar to the other.…”
Section: Discussionmentioning
confidence: 99%
“…Lemoine et al [ 18 ] found a strong correlation between MDCT and fluorescent microspheres when measuring renal perfusion. Several previous studies demonstrated that MDCT perfusion was a useful method for renal functional evaluation [ 19 22 ]. However, the perfusion information in those early studies was obtained by sequential scans in a certain part of the kidney due to the limited coverage of detectors using conventional MDCT.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the medullary BF values were not measured in previous studies. Furthermore, BF values in UUO could not be compared with previous studies [ 14 , 19 , 29 , 30 ] because of different CT system, perfusion post-processing algorithms and research subjects.…”
Section: Discussionmentioning
confidence: 99%